FINANCIAL INCLUSION AND ITS ROLE IN POVERTY REDUCTION IN IRAQ - Al-Husseini, Mohammed Ghali (PT. Antis International Publisher, 2026)
Objective: This research aims to demonstrate the importance of financial inclusion as a means to reduce poverty. Method: The study relied on a statistical population represented by the Iraqi banking sector for the period (2018-2022), as this period provides insight into the realities and challenges facing financial inclusion. The research also employed an analytical approach to the dimensions and indicators of financial inclusion for assessment. Results: Consequently, a set of conclusions was reached, the most important of which is the low levels of financial inclusion dimensions in Iraq despite an increase in the composite financial inclusion index. Novelty: In recent years, there has been growing interest in financial inclusion, achieved through the provision of advanced banking services via internet or mobile networks, in addition to extending banking services to the largest possible number of societal segments, particularly those with limited income. Therefore, the research concludes that the monetary authority, as the body responsible for diversifying opportunities to enhance financial inclusion, must conduct precise follow-up on the plans it has developed within the frameworks of the treatments prepared for this purpose.